Elaboración de una guía nutricional para fomentar hábitos alimenticios adecuados, para los niños (as), que acuden al bar escolar de la Escuela fiscal mixta Carlos Julio Arosemena, de la ciudad de Quevedo, año 2013 - Benítez Navarrete, Paola Maribel (2013)
This research was conducted at the Carlos Julio Arosemena Tola. Attorney School, located in the area of Atascoso in the canton of Quevedo, it contains a large number of students distributed among 14 classrooms. It was raised as a main objective the development of a nutritional guide to promote eating habits. For this reason, many children and teachers were used, with the desire to know how they were related to healthy food consumption as well as the large number of junk food that is sold in schools. Nowadays, poor nutrition in educational institutions is changing slowly, it is still being performed as routine manner when it needs to be properly treated as a technique to achieve efficiency in order to provide adequate Food, varied and nutritious. By far, school populations develop poor eating habits, making students lower their performance. While homemade and natural foods are not being served, junk food is reaching great levels of intake and it is being chosen in many places for their high consumption and profitability. Children spend a high percentage of their lives in schools where they consume lots of foods that are available to them through the kiosks, bars, canteens, school canteens; in addition to that, lunch boxes are being prepared improperly which increases the risk of health and nutritional deficiency. There are several drawbacks to feeding problems such as: the introduction of foreign foods to our environment and customs, excess refined sugars, and a lot of children with poor nutrition habits. The development of the nutrition guide is designed to encourage healthy habits throughout the school family, letting them know the benefits and the advantages of consuming healthy foods on a daily basis.